The Role of the Need for Cognition towards Student’s Mathematics Self-Efficacy - Widya Dwiyanti; Y.L. Sukestiyarno; Mulyono Mulyono; Walid Walid (International Conference on Science, Education, and Technology, 2022)
Abstract. Numerous research has established the impact of mathematical self-efficacy on an individual's ability to successfully solve mathematical tasks. However, according to the need for cognition paradigm, the element of difficulty in mathematics is also connected to both high and low degrees of cognitive function participation. This study intends to evaluate the contribution of one's need for cognition to one's degree of mathematical self-efficacy. 40 students studying at Mathematics Education Department in Sebelas April University Sumedang, Indonesia, participated in this study. The need for cognition and mathematical self-efficacy questionnaires, which used Likert scale scoring, were used to gather the data, which was then analyzed using correlational and regression methods. The findings revealed a significant and strong correlation between student need for cognition and mathematical self-efficacy. In addition, the need for cognition has also been shown to have a significant and positive impact on students' mathematical self-efficacy. This means that a higher level of student needs for cognition will lead to a higher level of mathematical self-efficacy.